BLOCKCHAIN AND OPEN INNOVATION: A LITERATURE REVIEW - BOUTAKY , Soukaina; SAHIB EDDINE , Abdelhak; EL MOUSADIK , Mouna (Revue Internationale du Chercheur, 2020)
The objective of this article is to understand how a groundbreaking technology like Blockchain can impact the process of open innovation. To achieve this, we have used very rich documentary research of two different disciplinary fields to produce fruitful literature. In fact, the literature on open innovation has two main streams depending on the point of view of the company or that of the interface between the company and its external partners. In this work, we focused on the second part, that of the open innovation interface, to analyze the contributions of Blockchain technology to this paradigm. This article constitutes a theoretical framework for Moroccan companies especially in this conjuncture characterized by the digital transformation.